(untitled) (Biological Sciences - PJSIR, 2000)
One new species Lackerbaueria fatigo representing the genus Lackerbaueria Zakhvatkin, 1941 is described from the hypopial stage. A key, comparison of characters, similarity matrix and phenogram are given to all the known species in this genus.